Multiple subcutaneous abscesses by Corynebacterium amycolatum in a patient with severe idiopathic aplastic anaemia - Yuka Shintani; Ayano Fukushima‐Nomura; Takeru Funakoshi; Masatoshi Sakurai; Jun Kato; Masahiro Fukuyama; Toyoko Inazumi; Kiyofumi Ohkusu; Hayato Takahashi (Wiley, 2024)
Abstract Corynebacterium amycolatum is a part of the normal skin flora and has been underestimated as a pathogen. However, in recent years, the species has gained recognition as an important pathogen causing severe infections, particularly in immunocompromised patients. Nevertheless, identifying these organisms at the species level is difficult in routine clinical microbiology, leading to limited knowledge of their clinical manifestations in infectious diseases. In this study, we report a rare case of multiple subcutaneous abscesses in a patient with severe neutropenia, wherein C.amycolatum was identified as the causative organism through genotyping tests. This case highlights the importance of this organism as an aetiological agent of severe skin infections in patients with compromised immune systems.